METHODS OF ASSESSING INVESTMENT EFFICIENCY IN LIGHT INDUSTRY - Л. Г. Кадирова (Web of Journals Publishing, 2026)
This article presents the theoretical foundations of investment attraction and management in the textile industry, scientific features of investment project organization and financing, and foreign experiences of investment efficiency evaluation.
Keywords: Investments, investment projects, export, quality, economic methods, methodology, world prices, arrived.